Short wavelength lasers and their applications - Whybrew, A; Whybrew, Adam (1996)
﻿ Most of this thesis describes experiments conducted in order to generate soft x-rays of energy >67 eV from a laser-generated plasma, in order to pump the Xe III Auger laser at 109 nm. In attempts to obtain the optimal sub-nanosecond laser pulses for amplification in a very simple KrF (248 nm) laser a compact KrF oscillator was used to obtain 1 ml pulses of FWHM duration 2 ns, and plasma-truncated reflection of a focused KrF beam from metal targets gave 1.8 ns pulses. Longer pulses were obtained by truncated stimulated Brillouin scattering (TRUBS), and by plasma-truncated spatial-filtering. Experiments were conducted to pump the Xe III laser using the leading edge of a 20 ns KrF laser pulse. An off-axis spherical mirror produced a 3 cm line plasma on a tantalum target. A poor conversion efficiency to soft x-rays was observed. Unexpectedly poor KrF beam quality was shown to have been a potential cause, a fault in the detection system having been ruled out. A repeat experiment was started, employing tighter focusing and better KrF beam quality. A 7 ps KrF laser system was also investigated for the generation of the necessary plasmas. No 109 nm lasing was observed, and a low conversion efficiency into soft x-rays was measured. The short duration of the KrF pulse was suspected as the cause, and some attempts were made to compensate for this by means of preformed plasmas. Over the course of the work, several aspects of KrF laser technology were improved, including: the characterisation of a novel, safe, solid-state source of fluorine (F2); the quantitative characterisation of nitrogen dioxide (NO2) as a variable attenuator for KrF radiation; and the manufacture of uniform, transparent, electrodes led to the laser system having the highest single pulse energy (2.55 J) of any UV-preionised, discharge-excited, conventional-aperture KrF laser. Finally, separate work led to the development and absolute characterisation of a laser-plasma source of tunable VUV/EUV/XUV radiation (30 nm to 200 nm; 6 eV to 41 eV), as well as a sodium salicylate scintillator-based detection system. After optimisation of the target material, laser focusing, and micro-channel-plate (MCP) focusing of the plasma emission, an output of between 106 and 107 photons per shot in a 4 nm bandwidth could be delivered on target.